World Wide Video Festival 1984. - Kijkhuis, Den Haag; World Wide Video Festival, Den Haag (Den Haag : Kijkhuis, 1984)
Almy, Max ; Robbins, Christine ; Ashley, Robert ; Alpert, Jon ; André, Marie ; Alvarez, Julián ; Blondeel, Michèle ; Barron, Ros ; Bourges, Alain ; Borelli, Caterina ; Borelli, Caterina ; Beutelschmidt, Thomas ; Gregor, Lutz ; Bouzat, Luc ; vom Bruch, Klaus ; Fendel, Heike-Melba ; Castillo, Juan ; etc.
World Wide Video Festival 1984, Kijkhuis, Den Haag, 4 - 9 september 1984
Nederlands & Engels
boek